ظهرة الهجرة غير الشرعية وأثرها على السياسة الخارجية اليبية - Musbah A.M. Aboukshame
Illegal immigration has become a global phenomenon and an obsession which raises safety concerns to countries of origin, transit and destination and it also affects the relations of many countries and left obvious effects on the International community in all segments of life including economic, political, social and demographic. In an attempt to find a solution to the phenomena, the idea came to undertake this study, titled: "Illegal immigration Phenomenon and its effects on the Libyan foreign policy" came about as a case study on the Libyan Foreign Affairs. The study aimed to identify the main reasons of illegal migration to Europe via the Libyan soil and also to identify the most important strategic ways and plans towards achieving cooperation among the countries of the world in dealing with the illegal immigration phenomenon. The study also aimed to identify on how the Libyan policies face the effects and damages caused by illegal immigration phenomenon. The study emphasized on the success of the Libyan legislation through criminalizing illegal immigration phenomenon in limiting the rise of illegal migrant numbers. The study relied in its methodology on past studies, reports, and data available from both the theoretical and technical through references or analysis drawn from population sample's data. The researcher used the inductive, analytical and descriptive approach and the study concluded with many important findings; accepting hypothesis of the study where the study indicates the reasons behind illegal migration to Europe via Libya soil and it also indicates illegal migration to Europe via Libya soil effects and damages on the Libyan community as well as it emphasizes that the Libyan legislation succeeded by way of criminalizing illegal immigration phenomenon in limiting the rise of illegal migrant numbers.